2021
DOI: 10.3390/ijgi10100681
|View full text |Cite
|
Sign up to set email alerts
|

Which Gridded Population Data Product Is Better? Evidences from Mainland Southeast Asia (MSEA)

Abstract: The release of global gridded population datasets, including the Gridded Population of the World (GPW), Global Human Settlement Population Grid (GHS-POP), WorldPop, and LandScan, have greatly facilitated cross-comparison for ongoing research related to anthropogenic impacts. However, little attention is paid to the consistency and discrepancy of these gridded products in the regions with rapid changes in local population, e.g., Mainland Southeast Asia (MSEA), where the countries have experienced fast populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…This analysis reinforces findings of other studies which find that currently available gridded population products tend to underestimate populations in urban areas [94][95][96], especially in higher-density poorer neighbourhoods [97]. For example, Tuholske and colleagues (2021) compared five gridded population products to estimate the proportion of population affected by natural disasters (SDG 11.5) in three regions where disasters had occurred, and found that 1x1km population estimates varied widely among data products, and reflected anywhere from 20% to 80% of the total UN estimated population in each region.…”
Section: Plos Onesupporting
confidence: 90%
“…This analysis reinforces findings of other studies which find that currently available gridded population products tend to underestimate populations in urban areas [94][95][96], especially in higher-density poorer neighbourhoods [97]. For example, Tuholske and colleagues (2021) compared five gridded population products to estimate the proportion of population affected by natural disasters (SDG 11.5) in three regions where disasters had occurred, and found that 1x1km population estimates varied widely among data products, and reflected anywhere from 20% to 80% of the total UN estimated population in each region.…”
Section: Plos Onesupporting
confidence: 90%
“…2 and 5 ), as their accuracy appears to be highly dependent on the completeness of identified building structures. The quality of the underlying satellite data containing information on built environments and the applied methodology to automatically extract built features involves omission and commission errors, leading to an under- or overestimation of uninhabited areas 21 , 49 , 50 . While WorldPop top–down constrained uses polygon building footprint data and HRSL uses high resolution satellite imagery (~50 cm), GHS-POP extracts built features from Landsat 8 imagery with a resolution of ~30 meters 32 .…”
Section: Resultsmentioning
confidence: 99%
“…While WorldPop top–down constrained uses polygon building footprint data and HRSL uses high resolution satellite imagery (~50 cm), GHS-POP extracts built features from Landsat 8 imagery with a resolution of ~30 meters 32 . Due to the difficulty of detecting built-up areas from coarser resolution satellite imagery, GHS-POP and, to a lower extent, LandScan have previously been found to overestimate uninhabited zones and thus underestimate people in sparsely populated sub-urban and rural areas 21 , 51 , 52 . We found similar patterns in two rural areas in Garissa and Nakuru counties in Kenya, where divergent patterns of settlement detection between the gridded population products were seen (Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the strengths and weaknesses of the WorldPop dataset, combined with the comparative analysis results of the released global gridded population datasets (including GPW, GHS-POP, WorldPop, and LandScan) by Yin et al . 34 , and considering the problem of data time series, we decided to use the unconstrained global population grids as the population input data for this study.…”
Section: Methodsmentioning
confidence: 99%